2021
DOI: 10.1186/s13018-021-02849-w
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative 3D imaging with cone-beam computed tomography leads to revision of pedicle screws in dorsal instrumentation: a retrospective analysis

Abstract: Background Correct positioning of pedicle screws can be challenging. Intraoperative imaging may be helpful. The purpose of this study was to evaluate the use of intraoperative 3D imaging with a cone-beam CT. The hypotheses were that intraoperative 3D imaging (1) will lead to an intraoperative revision of pedicle screws and (2) may diminish the rate of perforated screws on postoperative imaging. Methods Totally, 351 patients (age 60.9 ± 20.3 a (15–9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…Therefore, other techniques, such as CBCT, have been developed to close this intraoperative gap. Additionally, good (type A + B according to Gertzbein) pedicle screw positions have been observed in 88.8–94.1% patients after dorsal instrumentation with intraoperative imaging by a CBCT scan [ 15 , 19 ]. Moreover, it has been shown that intraoperative imaging with CBCT is not inferior to intraoperative CT [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other techniques, such as CBCT, have been developed to close this intraoperative gap. Additionally, good (type A + B according to Gertzbein) pedicle screw positions have been observed in 88.8–94.1% patients after dorsal instrumentation with intraoperative imaging by a CBCT scan [ 15 , 19 ]. Moreover, it has been shown that intraoperative imaging with CBCT is not inferior to intraoperative CT [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, pedicle screws were inserted and cannulated over previously inserted Kirschner wires during dorsal instrumentation, and the intraoperative imaging procedure was performed as previously described [ 15 ]. The decision whether intraoperative CBCT imaging was performed was made by the surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…Des Weiteren können somit die Anzahl der Revisionseingriffe reduziert und die damit einhergehenden Risiken und zusätzlichen Kosten vermieden werden. Der Einsatz der CBCT in der Wirbelsäulenchirurgie führt in Abhängigkeit von der Literatur in bis zu 7 % der Fälle zur intraoperativen Korrektur von Implantatlage oder Reposition [6]. Zudem konnte aufgezeigt werden, dass die Sensitivität bei der Visualisierung von Kortikalisverletzungen durch Pedikelschrauben an der Wirbelsäule vergleichbar ist mit dem postoperativen CT [18].…”
Section: Intraoperative Bildgebungunclassified
“…Untersuchungen, die sich mit postoperativen Revisionsraten bei dorsalen Instrumentierungen der Wirbelsäule beschäftigen, haben bereits gezeigt, dass der Einsatz der intraoperativen 3-D-Bildgebung einen positiven Effekt auf die Schraubenplatzierung hat. Intraoperative Fehllagen konnten, aufgrund der zusätzlichen Informationen aus den 3-D-Datensätzen erkannt und unmittelbar korrigiert werden [6,9]. Darüber hinaus bieten Navigationstechniken in Kombination mit einer intraoperativen CBCT (Cone-Beam-Computertomografie) oder CT durch eine präzise Planung von Schraubengröße und -trajektorie die Möglichkeit, eine Implantatfehllage zu verhindern [6,10,11].…”
unclassified
See 1 more Smart Citation